2018
DOI: 10.1002/anie.201810891
|View full text |Cite
|
Sign up to set email alerts
|

Substrate‐Induced Self‐Assembly of Cooperative Catalysts

Abstract: Dissipative self-assembly processes in Nature rely on chemical fuels that activate proteins for assembly through the formation of a noncovalent complex. The catalytic activity of the assemblies causes fuel degradation, resulting in the formation of an assembly in a high-energy, out-of-equilibrium state. Herein, we apply this concept to a synthetic system and demonstrate that a substrate can induce the formation of vesicular assemblies, which act as cooperative catalysts for cleavage of the same substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 56 publications
(47 reference statements)
2
42
0
Order By: Relevance
“…Prins and Chen et al. demonstrated that a phosphate ester substrate can induce the formation of vesicular assemblies, which act as cooperative catalysts for hydrolysis of the same substrate . A substrate‐induced covalent assembly formation of chiral boroxinate catalysts has also been shown by Wulff et al.…”
Section: Methodssupporting
confidence: 71%
“…Prins and Chen et al. demonstrated that a phosphate ester substrate can induce the formation of vesicular assemblies, which act as cooperative catalysts for hydrolysis of the same substrate . A substrate‐induced covalent assembly formation of chiral boroxinate catalysts has also been shown by Wulff et al.…”
Section: Methodssupporting
confidence: 71%
“…[28,29] Substrate-induced access of active conformation is also widely exploited in extant biology for accelerating catalysis. [33][34][35][36] In the present work, we show the out-of-equilibrium generation of ac onformationally distinct assembled state induced by substrate,accelerated catalysis,and relapse to the initial state ( Figure 1b). Simple amino acid based amphiphiles have been shown to access out-of-equilibrium helical morphology in presence of ak inetically stable ester.W es how evidence of the time-dependent generation of an ew phase, rate acceleration negative feedback and disassembly.…”
supporting
confidence: 59%
“…Inspired by biological system, research interests in supramolecular chemistry are now shifting to the implementation of out-of-equilibrium selfassembly in artificial scenario. [5] An important focus of out-ofequilibrium self-assembly is the selection of specific selfassembly pathways along ac orrugated self-assembly energy landscape,that leads to products temporarily or permanently retained in alocal rather than the global minimum. In recent efforts,s pecific pathways are selected through the employment of,e .g., rationally designed molecules, [6] or catalysts, [7] and features the formation of different out-of-equilibrium structures bearing different material properties while still employing the same building blocks.Despite these prospects, the current approaches towards kinetically controlled selfassembly remain scarce.…”
mentioning
confidence: 99%